2018
DOI: 10.1186/s12966-018-0731-z
|View full text |Cite
|
Sign up to set email alerts
|

What strategies do desk-based workers choose to reduce sitting time and how well do they work? Findings from a cluster randomised controlled trial

Abstract: BackgroundLarge amounts of sitting at work have been identified as an emerging occupational health risk, and findings from intervention trials have been reported. However, few such reports have examined participant-selected strategies and their relationships with behaviour change.MethodsThe Stand Up Victoria cluster-randomised controlled trial was a workplace-delivered intervention comprising organisational, environmental and individual level behaviour change strategies aimed at reducing sitting time in desk-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…This opens up both challenges and opportunities for GPs regarding their levels of sedentary behaviour [ 52 , 53 ]. It does, however, mean that GPs now have more in common with workers in other medical and non-medical environments, such as office and call centre workers, where interventions targeted at reducing levels of sedentary behaviour have had varying levels of success [ 54 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This opens up both challenges and opportunities for GPs regarding their levels of sedentary behaviour [ 52 , 53 ]. It does, however, mean that GPs now have more in common with workers in other medical and non-medical environments, such as office and call centre workers, where interventions targeted at reducing levels of sedentary behaviour have had varying levels of success [ 54 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Users indicated that they preferred to use the standing workstation when completing work tasks which did not require high levels of concentration, such as sending emails. Specific work tasks associated with standing have also been indicated in other studies [ 22 , 25 , 40 ]. Moreover, a recent study found that people did not identify “sitting” as an activity in and of itself, but rather thought of sitting in relation to the task they performed (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…Individual office workers seem to use many different strategies to reduce their sitting time and replace it with standing or physical activity. In the Stand-Up Victoria study, 82 separate strategies were identified by participants [ 22 ]. In another study, the behaviour change wheel [ 23 ] was used to develop a tailored intervention to reduce sitting, which identified 39 behaviour change techniques [ 24 ] aimed at providing information, rewards, and prompts for reducing sitting time [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This opens up both challenges and opportunities for GPs regarding their levels of sedentary behaviour (52,53). It does, however, mean that GPs now have more in common with workers in other medical and non-medical environments, such as o ce and call centre workers, where interventions targeted at reducing levels of sedentary behaviour have had varying levels of success (54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%